The implementation of stakeholder engagement and its impact on CSR : the case of Deloitte - Le, Anna Van Anh (2017)
Purpose: The research pursues to understand how stakeholder engagement is implemented and how it impacts an organization’s corporate social responsibility. Methodology: The study applies a qualitative, explorative and partially grounded-theory method. Primary and secondary data is applied in form of archival data, industry reports, and a single-case study that entails twelve interviews taken place on a personal, telephone and Skype basis. The researched firm is Deloitte, the largest private provider for professional services in the management-consulting industry. Findings: The research delineates seven phases that are approached to implement stakeholder engagement. Hereby, insights into their impact on CSR are explored. Based on the data collection, the outcomes and challenges of stakeholder engagement are elaborated. Research implications: Based on the AA1000SES standard a revised framework was created for managerial practitioners. Thus, an improved and simplified concept is described, which ultimately guides a firm to realize its CSR activities. Further, it explores weaknesses of the realization process, and which type of CSR leadership is used in the management-consulting industry. Practical implications: In order to increase the effectiveness of the stakeholder engagement procedure, the research provides solutions to overcome the explored weaknesses.